PENGARUH SENAM OTAK TERHADAP MOTIVASI BELAJAR ANAK POS PAUD KENANGA DESA PULAU BIRANDANG KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Laila Ayu Insyani; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on survey result on children’s learning motivation, Pos PAUD Kenanga were in the low category, so need to aplicated Brain Gym. This research aims to determine the effect of Brain Gym on children’s learning motivation in Pos PAUD Kenanga Pulau Birandang Village of Kampar Timur District of Kampar Regency. This reaserch is an experiment research with use One Group Pre-test Post-test Design. The sample of this reaserch is 10 childrens. The data collection techniques were used observation. The data analysis used t-test with SPSS 23.0 programs. The analysis data result that tcount = 19.900 and sig = 0,000 with ttable = 2,262, cause tcount ˃ ttable with level sig 0,05. So Ho rejected and Ha accepted that there were the significant differences in children’s learning motivation between before and after used Brain Gym, and can be concluded that the effect of Brain Gym on children’s learning motivation in Pos PAUD Kenanga Pulau Birandang Village of Kampar Timur District of Kampar Regency were in 37,93% with middle category.Key Words: Brain Gym, Children’s Learning Motivation